Change the gymnastics minimum age requirements and the changes that have occurred in major competitions in women's artistic gymnastics - Atikovic, A.; Delaš Kalinski, S.; Cuk, I. (Acta Kinesiologica, 2017)
The Olympic Games (OG) and World Championships (WC) represent the crown of each athlete`s career, so it is the same with gymnasts. The aims of this study it was investigate the historical analysis of the chronological age trend of all participants of women`s artistic gymnastics who have won medals in the period between 1928 and 2016 has been made. The examinees were gymnasts who had won medals at the following competitions: OG from 1928 to 2016 (n = 655) and WC from 1934 to 2015 (n = 997). If we compare the age of the WAG by disciplines, the oldest gymnasts are on the BB with an average age on (OG 20.88 ± 4.93) and on VT (WC 19.79 ± 4.17) years old, and the youngest in the FX (OG 20.24 ± 4.14) and BB (WC 18.38 ± 3.62). The results of independent t test were significant difference between OG and WC on All-around individual (AAI), Valuting table (VT), Uneven bars (UB), Balance beam (BB), Floor (FX), and second place on AAI, BB and FX. Since artistic gymnastics becomes each Olympic cycle over more demanding in terms of complexity and difficulty value of the elements, it is expected fact that gymnasts need more time to acquire stability, experience and safety when performing such complex exercises in future.